Pistacia atlantica, a spontaneous hypermycotrophic phanerophyte: could be a natural tool to enhance the potential of mycorrhizal infectivity (PMI) of soils in arid regions? - Limane A.; Smail-Saadoun N. (XVI GREMPA Meeting on Almonds and Pistachios, 2016)
In our drylands, spontaneous perennials species should be used to play the role of facilitator species in the success of plurispecific agro-ecosystems. It is the case of Atlas pistachio (the main spontaneous phanerophyte in Algerian pastoral steppe). The mycorrhizal status of this species could potentially increase the potential of mycorrhizal infectivity (PMI) of soils in drylands and benefit these poor soils by its rhizospheric effect. In Algeria, we have chosen for this study, two populations of Pistacia atlantica. The first one is located in semi-arid region (province of Médéa) and the other in hyper arid region (province of Béchar). We found that all the roots of the studied samples were infected by Arbuscular Mycorrhizal Fungi (AMF). Identification of their spores showed that Atlas pistachio is a hypermycotrophic species. At least we found 5 different species of Glomeromycetes in the first population (Médéa) and 3 different species in the second one (Béchar). It may be a reservoir of AMF propagules which will potentially infect cultivated species and thus will enhance their yields.
16. Meeting of GREMPA (Groupe de Recherches Méditerranéennes pour l\'Amandier et Pistachier / Mediterranean Research Group for Almond and Pistachio), 2015/05/12-14, Meknes (Morocco)